Hitchcock’s appetites : the corpulent plots of desire and dread (2016)
F rom the time Alfred Hitchcock made his historic 1939 move from Shamley Green, outside London, to Los Angeles to work in Hollywood, until his death forty years later, no publicity piece, film review, or interview with the director was complete without at least a perfunctory reference to, or a loving jab at, his formidable physique. Before he had even acquired that most familiar of monikers, “The Master of Suspense,” in 1942, he had been embraced by the American press with headlines like “300-Pound Prophet Comes to Hollywood,” “Heavy Heavy . . . Hitchcock,” and “Director Hitchcock, Big As An Elephant.” A publicity still for his first American picture Rebecca reassured us, “‘Hitch’ doesn’t mind allusions to his 239 pounds.” Since his passing, the many biographical and critical accounts of the man and his work have continued to find references to his weight, size, or appetites, to be de rigueur. Whether these references function as amusing anecdotes about an idiosyncratic auteur, or as more serious and penetrating ruminations on the driving compulsions of his life, they seem to suggest Hitchcock’s fatness as a fundamental truth about him.